2021
DOI: 10.1016/j.heliyon.2021.e08197
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antihemolytic properties of a CNF/AgNP-chitosan film: A potential wound dressing material

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
0
4
0
3
Order By: Relevance
“…The enhancement of the antioxidant activity of AP-CSLNs originated from the combination of two effects: the inherent antioxidant properties of AP itself and the enhanced delivery provided by the nanocarriers [ 39 ]. Sharma et al (2019) detected higher antioxidant activity in curcumin-loaded NPs compared to free drugs [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of the antioxidant activity of AP-CSLNs originated from the combination of two effects: the inherent antioxidant properties of AP itself and the enhanced delivery provided by the nanocarriers [ 39 ]. Sharma et al (2019) detected higher antioxidant activity in curcumin-loaded NPs compared to free drugs [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The absorption peak at 1060 cm −1 was associated with the stretching vibration of the C-O-C bond on the pyran ring. The absorption peak at 897 cm −1 was attributed to the stretching vibration of the β-1, 4-glycosidic bond between cellulose molecules and the deformation vibration of O-H in the hydroxyl group of the sample that absorbed water molecules [ 32 , 33 ]. As for CUR, the broad absorption band at 3504 cm −1 represented a representative peak of the phenolic OH group’s stretching vibration.…”
Section: Resultsmentioning
confidence: 99%
“…Hasibuan et al synthesized chitosan/cellulose composite films incorporated with AgNPs. The in vitro experiments revealed that the films containing nanoparticles induced the strongest inhibition zone when cultured with B. subtilis and P. aeruginosa , revealing excellent antibacterial activity suitable for bacterial-infected wound care [ 132 ].…”
Section: Chitosan-based Scaffolds Incorporated With Silver Nanoparticlesmentioning
confidence: 99%